Pulsed Electric Field Extraction of α and β-Acids From Pellets of Humulus lupulus (Hop) - Ntourtoglou, George; Tsapou, Evangelia Anastasia; Drosou, Fotini; Bozinou, Eleni; Lalas, Stavros; Tataridis, Panagiotis; Dourtoglou, Vassilis (Frontiers in Bioengineering and Biotechnology, 2020)
The subject of this study was the extraction of bitter acids and terpenes from hop pellets using Pulsed Electric Field (PEF) as well as the comparison of the effect of PEF technique between two hop varieties (one bitter and one aromatic). To evaluate the effect of PEF on the compounds responsible for the bitterness of hops, the concentration of α-acids and β-acids (humulone and lupulone) was measured. Concerning the aromatic character, the hops volatiles caryophyllene, humulene and β-myrcene were studied both with and without PEF treatment. For the analysis of the acids and the volatile substances, a traditional UV-VIS spectrophotometer technique was used followed by gas chromatography coupled with mass spectrometry. The latest was applied to the extracts previously purified through a Graphitized Carbon Black syringe for Solid Phase Extraction. The results showed that PEF had a significantly positive impact on the bitterness of bitter hops (increase of more than 20% in α-acids extraction), while regarding its aromatic character a slightly increase in the concentration of the volatile compounds (5.6 and 7.4% for humulene and caryophyllene, respectively) was observed. Concerning the aromatic variety of hops, no impact of the PEF treatment was noticed.